Electrochemical Approaches to "Living off the Land" in Space. (March 2020) - Jackson, Gregory S.; Elangovan, S.; Hintze, Paul E.
Abstract : The incredible expense of sending resources out of Earth's gravity well to space predicates that systems for long-term space operations rely on resources already available in space for energy and materials. Such in-situ resource utilization (ISRU) can harness ubiquitous solar energy and its conversion to electricity. As such, electrochemistry has been recognized as a critical path for converting low-value compounds and materials in space into valuable products such as fuel, oxygen, structural materials, and functional materials/devices to support proposed space operations. Recent advances in electrolysis for splitting water and CO2 and in systems for reducing oxides provide promise for advancing ISRU. As demonstrated by the successful MOXIE development to provide a small-scale CO2 electrolysis unit to Mars, development of robust autonomous electrochemical systems for near-term ISRU presents unique challenges. Nonetheless, the potential rewards of such development for space operation as well as terrestrial technology deployment can be enormous.